1993
DOI: 10.2307/4088657
|View full text |Cite
|
Sign up to set email alerts
|

Common Grackle Anting with Lime Fruit and Its Effect on Ectoparasites

Abstract: A, nting is stereotyped behavior in which birds expose themselves to fluid-secreting ants or other pungent substances. During "active" anting a bird crushes an ant in the bill and rubs it frenetically through its plumage (Rothschild and Clay 1952). During "passive" anting a bird entices ants to crawl through its plumage by crouching or lying on an ant hill with spread wings and tail. Although anting has been recorded for more than 200 avian species, most of them passerines, its adaptive significance remains co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Although lime juice had no effect, exposure to vapor from the lime rind rapidly killed the lice. This result is not surprising, given that lime peel contains D-limonene, a monoterpene present at high concentrations in the peel oil of many citrus fruits, and which is known to be toxic to a wide variety of arthropods [194]. Nevertheless, the hypothesis that birds use citrus peel, or any of the other substances listed above, as a means for actually controlling their ectoparasites is still in need of in vivo testing.…”
Section: Number Of Licementioning
confidence: 85%
See 2 more Smart Citations
“…Although lime juice had no effect, exposure to vapor from the lime rind rapidly killed the lice. This result is not surprising, given that lime peel contains D-limonene, a monoterpene present at high concentrations in the peel oil of many citrus fruits, and which is known to be toxic to a wide variety of arthropods [194]. Nevertheless, the hypothesis that birds use citrus peel, or any of the other substances listed above, as a means for actually controlling their ectoparasites is still in need of in vivo testing.…”
Section: Number Of Licementioning
confidence: 85%
“…Clayton and Vernon [194] performed one such test. The authors observed a Common Grackle (Quiscalus quiscula) anointing itself with half a lime fruit.…”
Section: Number Of Licementioning
confidence: 99%
See 1 more Smart Citation
“…Plumage maintenance behaviours include preening by the bill and scratching by the foot; louse burdens increase dramatically after experimental impairment of preening (Clayton, 1991). Bathing, dust-bathing, sunning (Moyer & Wagenbach, 1995) and usage of aromatic herbs (Clayton & Vernon, 1993) probably also play some role in controlling louse burdens. However, the distribution and efficacy of these behaviours are unclear.…”
Section: The Bird-louse Relationshipmentioning
confidence: 99%
“…AVIAN CHEMICAL DEFENSE HAS been discussed in the context of ectoparasites (Simmons 1966, Ehrlich et al 1986, Clayton and Vernon 1993, Dumbacher 1999; but, heretofore no published experiments have speciÞcally addressed mosquitoes. We suggest that birds may use endogenous or exogenous chemicals to repel mosquitoes and other ectoparasites in a manner analogous to human and nonhuman primates (Berenbaum 1995, Valderramma et al 2000, Weldon et al 2003.…”
mentioning
confidence: 99%